Director With Foreign Experience, Accounting Conservatism And Tax Avoidance - Aldriana, Frigrita; Marlinah, Aan (Media Bisnis, 2024)
Abstract: This research is a development of previous research, namely (Wen et al. 2020)with the dependent tax avoidance and the independent variable director with foreign experience. The reason for this research is to analyze empirical evidence regarding the influence of directors with foreign experience and other factors on tax avoidance in cyclical and noncyclical companies. The variables used in this research are directors with foreign experience on the board, profitability, firm size, leverage, independent directors with foreign experience, directors with foreign experience on audit committee, and accounting conservatism are the factors used in this study.The population of this research is all cyclical and noncyclical companies listed on the Indonesia Stock Exchange from 2020 to 2022. The sample was selected using a purposive sampling method, and 189 data were taken. The data analysis method used is multiple regression analysis.The research results show that firm size have a positive influence on tax avoidance. Independent directors with foreign experience have a negative effect, while other independent variables such as directors with foreign experience on board, profitability, Leverage, directors with foreign experience on audit committee, accounting conservatism have no effect on tax avoidance. Abstrak: Penelitian ini adalah pengembangan dari penelitian sebelumnya yaitu (Wen et al. 2020) dengan variabel dependen penghindaran pajak dan variabel independent director with foreign experience. Alasan dari penelitian ini adalah untuk menganalisis bukti empiris mengenai pengaruh director with foreign experience dan faktor lainnya terhadap penghindaran pajak pada perusahaan cyclical dan noncyclical. Variabel yang digunakan dalam penelitian ini adalah director with foreign experience in the board, profitability, firm size, leverage, independent directors foreign experience, director with foreign experience on audit committee, dan accounting conservatism. Populasi penelitian ini adalah semua perusahaan cyclical dan noncyclical yang terdaftar di Bursa Efek Indonesia selama tahun 2020 sampai dengan tahun 2022. Sampel dipilih dengan menggunakan metode purposive sampling, dan diambil 189 data. Metode analisis data yang digunakan adalah analisis regresi berganda. Hasil penelitian menunjukkan bahwa firm size memiliki pengaruh positif terhadap penghindaran pajak. Independent directors foreign experience berpengaruh negatif, Sedangkan variable independen lainnya seperti directors with foreign experience in board, profitability, leverage, directors with foreign experience on audit committee, accounting conservatism tidak memiliki pengaruh terhadap penghindaran pajak.